(3GdYdGbI Hjf GdhaGA HGdYbhO GdfaSjI h SdhcjGJ GdehGWfI GdJfXjejI (B: s (3HMK JWHjbi (B/ s - (3eQje CMeO YHOGdJhGH eMeOs; (3YGOd eMeO YHOGdMdje RGjO (B: s ((3GdbGgQI (B: s (3eQje CMeO YHOGdJhGH eMeO (B: s, 2021)
(3GdgOa GdQFjSi ef gPg GdOQGSI gh OQGSI GdYdGbI Hjf GdhaGA HGdYbhO GdfaSjI h SdhcjGJ GdehGWfI GdJfXjejI ai GdLGeYGJ(B. (3h bO Je JcQjS bOQ cHjQ ef GdCHMGK dOQGSI CHYGO GdhaGA HGdYbhO GdfaSjI HWQb eNJdaI(B: (3JTed gPg GdCHYGO (B((3GdJRGeGJ GdbjGOI GdLjOI (B- (3GdJRGeGJ GdYOGdI h GdCfUGa (B- (3GdJRGeGJ eMJhi GdhXjaI (B- (3GdJRGeGJ JfehjI (B- (3GdJRGeGJ GLJeGYjI h CcGOjejI(B). (3h bO CgJe GdYOjO ef GdHGMKjf HSdhcjGJ GdehGWfI GdJfXjejI ai GdEOGQI(B: (3h CTGQJ GdYOjO ef GdOQGSGJ Edi Cf GdhaGA HGdYbhO GdfaSjI jJHYg GdYOjO ef GdSdhcjGJ GdEjLGHjI ai GdefXeGJ h Cf GdSdhcjGJ GdehGWfI GdJfXjejI JajO GdefXeGJ ai eSjQgG h SYjgG dJMbjb Gdfeh h ceG CTGQJ GdHGMKI dCgejJgG CjVG Ydi eSJhi GdLGeYGJ(B. (3h bO bGeJ GdHGMKI HJWhjQ GdaQhV ddJMbjb ai GdYdGbI GdEMUGFjI GdeJhbYI Hjf CHYGO GdhaGA HGdYbhO GdfaSjI h CHYGO SdhcjGJ GdehGWfI GdJfXjejI (B((3GdEjKGQ (B- (3GdcjGSI(B-(3GdQhM GdQjGVjI (B- (3GdSdhc GdMVGQi (B- (3GdVejQ GdMi(B) (3h Je GNJjGQ YjfI JMcejI ef (B200 (3gjFI eYGhfI ai GdcdjGJ JLGQI h fOSI ai LGeYJi GdbGgQI h CcJhHQ(B. (3h Je LeY GdHjGfGJ GdChdjI HGSJNOGe bGFeJi GSJHjGf(B. (3Je JUeje GdGSJHjGf GdChd dbjGS GdCHYGO GdSJI ddhaGA HGdYbhO GdfaSjI(B: (3ai Mjf Je GSJNOGe GdGSJHjGf GdKGfi dbjGS GdCHYGO GdNeSI dSdhcjGJ GdehGWfI GdJfXjejI(B. (3h JTjQ GdfJGFL GdQFjSjI dgPg GdOQGSI Edi hLhO YdGbI EjLGHjI Hjf GdhaGA HGdYbhO GdfaSjI h SdhcjGJ GdehGWfI GdJfXjejI(B. (3LejY GdfJGFL GdCNQi CjOJ GdaQVjI GdCSGSjI(B. (3h dcf fJGFL GdOQGSI GdMGdjI ChVMJ Cf CHYGO GdhaGA HGdYbhO GdfaSjI GdeJeKdI ai eMJhi GdhXjaI (B- (3GdJRGeGJ GdeGOjI (B- (3GdJRGeGJ GdGLJeGYjI h GdCcGOjejI (B- (3GdYOGdI h GdEfUGa(B) (3GNJdaJ eY GdOQGSGJ GdSGHbI(B: (3MjK ChVMJ Cf dG jhLO YdGbI Hjf GdCHYGO h SdhcjGJ GdehGWfI GdJfXjejI(B. (3h dcfgG GJabJ ai GdGdJRGeGJ GdhXjajI h GdegfjI h GdTNUjI (B((3GdJfehjI(B) (3eY SdhcjGJ GdehGWfI GdJfXjejIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJLGQI (B- (3bSe EOGQI GdCYeGds
(3UOQ GjVG cbQU eOeLs
Keywords: (3EOGQI GdCYeGds; (3GdhaGA HGdYbhO GdfaSjIs; (3SdhcjGJ GdehGWfI GdJfXjejIs